Evaluation of Antimicrobial Activity Using Cadmium Oxide Nanoparticles Prepared by Physical Method (PLAL) - Nisreen Kh. Abdalameer; Tuqa A. Khaleefa (Ibn Al-Haitham Journal for Pure and Applied Sciences)
The present study employed the pulsed laser ablation in liquid (PLAL) technique to synthesize cadmium nanoparticles (CdO NPs). PLAL is a top-down physical method that operates by splitting the precursor mass of metal ions into metal atoms. This work utilized a nanosecond Nd-YAG laser with two wavelengths, specifically 1064 nm and 532 nm, at a laser energy of 250 mJ. 250 pulses were applied for each wavelength during the synthesis process. This approach enabled the production of high-purity nanoparticles. The characteristics of the nanoparticles that were created were examined by the use of UV-Vis, and XRD analysis techniques. The antibacterial and antifungal properties of the tested substance were evaluated against two Gram-positive bacteria, namely Staphylococcus aureus and Streptococcus mutans, as well as two Gram-negative bacteria, specifically Escherichia coli and Pseudomonas aeruginosa. These bacterial strains were obtained from the oral cavity. Additionally, a specific genus of fungi known as Candida exists. The findings of the study indicate that CdO NPs synthesized using the PLAL technique possess antibacterial properties, rendering them effective in eradicating pathogenic bacteria and fungi.